In vivo measurements of lead in bone at four anatomical sites: long term occupational and consequent endogenous exposure. Issue 9 (September 1992) - Erkkilä, J; Armstrong, R; Riihimäki, V; Chettle, D R; Paakkari, A; Scott, M; Somervaille, L; Starck, J; Kock, B; Aitio, A
Abstract : Measurements of bone lead concentrations in the tibia, wrist, sternum, and calcaneus were performed in vivo by x ray fluorescence on active and retired lead workers from two acid battery factories, office personnel in the two factories under study, and control subjects. Altogether 171 persons were included. Lead concentrations in the tibia and ulna (representative of cortical bone) appeared to behave similarly with respect to time but the ulnar measurement was much less precise. In an analogous fashion, lead in the calcaneus and sternum (representative of trabecular bone) behaved in the same way, but sternal measurement was less precise. Groups occupationally exposed to lead were well separated from the office workers and the controls on the basis of calculated skeletal lead burdens, whereas the differences in blood lead concentrations were not as great, suggesting that the use of concentrations of lead in blood might seriously underestimate lead body burden. The exposures encountered in the study were modest, however. The mean blood lead value among active lead workers was 1.45 mumol l-1 and the mean tibial lead concentration 21.1 micrograms (g bone mineral)-1. The kinetics of lead in the tibia appeared to be noticeably different from that in the calcaneus. Tibial lead concentration increased consistently both as a function of intensity of exposure and of duration of exposure. Calcaneal lead concentration, by contrast, was strongly dependent on the intensity rather than duration of exposure. This indicated that the biological half life of lead in calcaneus was less than the seven to eight year periods into which the duration of exposure was split. Findings for retired workers clearly showed that endogenous exposure to lead arising from skeletal burdens accumulated over a working lifetime can easily produce the dominant contribution to systemic lead concentrations once occupational exposure has ceased.